Mayson, french, and ryan on company law 38e - French, Derek (New York : Oxford University Press, 2023)
"A Academic studies 20 Accounts disclosure of directors remuneration 436-40 dividend justification 253-4 Acting for a company agency see Agency attribution identification theory 649-50 when attribution will not be made 654-6 whose acts or thoughts 650-4 authentication and execution of documents see Authentication and execution of documents"--